2006
DOI: 10.1300/j005v31n01_12
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 12

Abstract: This study examined the perspectives and definition of leadership by women and mothers with children (n = 40) affiliated with Oxford Houses, a communal mutual-help recovery setting. Participants were asked questions relating to their experiences living in an Oxford House including the strengths and challenges encountered and how leadership impacted the stability in their house. Results illustrated the value of female leadership and highlighted the characteristics deemed important for women leaders in Oxford Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The use of grounded theory allows the researcher to think about the data in new ways, including finding new insights and rendering hidden assumptions visible (Charmaz, 2006). In the context of Oxford House, grounded theory has been used to understand how participants think about leadership in a women’s Oxford House (Davis et al, 2006; Timpo et al, 2014) and Latinos’ perceptions of living in an Oxford House (Alvarez et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…The use of grounded theory allows the researcher to think about the data in new ways, including finding new insights and rendering hidden assumptions visible (Charmaz, 2006). In the context of Oxford House, grounded theory has been used to understand how participants think about leadership in a women’s Oxford House (Davis et al, 2006; Timpo et al, 2014) and Latinos’ perceptions of living in an Oxford House (Alvarez et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…This could inspire Oxford Houses to develop strategies to improve the experience of female residents, and encourage more women to become leaders [8]. This is especially important, as this study has found that being involved in leadership positions can contribute to a positive recovery process.…”
Section: Discussionmentioning
confidence: 99%
“…Although the qualities that women in Oxford House look for in their leaders has been studied [8], no previous studies have examined the experiences of women who have taken on leadership roles in the Oxford House World Services. This qualitative study used grounded theory to explore factors contributing to women’s participation in leadership roles within the Oxford House organization.…”
Section: Introductionmentioning
confidence: 99%
“…Davis et al [8] studied how women and mothers with children living in Oxford Houses defined leadership and their perspectives on the strengths and challenges associated with being a leader. This qualitative study found the women emphasized the importance of mutual support in the process of recovery.…”
Section: Introductionmentioning
confidence: 99%